PERENCANAAN FASILITAS PARIWISATA (TOURISM AMENITIES) PANTAI PANDAWA DESA KUTUH KUTA SELATAN BADUNG - Putu Shintani Utari; I Made Adikampana (JURNAL DESTINASI PARIWISATA, 2014)
ABSTRACT The purpose of this study is to investigate and identify the potential in Pandawa Beach , South Kuta Kutuh village and is able to determine and analyze the planning of tourism facilities (tourism amenities) at Pandawa Beach Village Kutuh South Kuta . The method used in this study is the type of data , qualitative and quantitative , primary and secondary data sources , data collection technique that uses observation , interviews , questionnaires and literature study . For the determination of informants technique using purposive sampling and accidental sampling . And analysis of data using qualitative and descriptive data analysis using quantitative descriptive analysis of the percentage . The results of the study discusses the potential of the Pandawas beach area is divided into components , namely tourism " 4 A " as the potential that must exist in a Travel Attractions covering of Attraction , Amenities, Accessibility , and Ancilary Service. As for planning Everyday is determined based on the results of the questionnaire using descriptive analysis percentages , based on motivation , activity , potency , access , facilities and cleanliness , number of restaurants, the addition of facilities , accommodations , and facilities that need to be added . From questionnaire , it can be determined planning in the form of a picture or sketch plan Pandawas beach amenities.